Corporate Social Responsibility Dan Dampaknya Terhadap Manajemen Laba - Fitriana, Nur (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to examine the effect of social responsibility and CSR disclosure on earnings management. The sample in this study is a manufacturing company listed on the IDX. The results of the study indicate that CSR has an effect on earnings management, while the disclosure of CSR has an impact on the economy and the environment on earnings management. The results of this study indicate that CSR activities carried out by the company will affect the level of earnings management carried out by the company